Validation of flourishing scale PERMA on prospective student educators - Nadhirah, Nadia Aulia; Ilfiandra; Ipah Saripah; Tiara Iskandar; Akhmad, Sudaryat Nurdin; Dody Hartanto; Syamsu Yusuf (Psikopedagogia, 2025)
This study aims to validate the growth scale in the context of educational students. This scale is based on Seligman's PERMA theory, which includes five dimensions: positive emotion, engagement, relationships, meaning, and achievement. The research method used a survey involving 305 students  of the education study program aged 18–25 who were selected using the non-probability sampling method with the convenience sampling type. Data were analyzed using the Rasch Model to determine the nature of the psychometric development scale. The analysis showed a 36.1% unidimensionality, indicating a good ability to measure the development construct. As many as 35 of the 55 items were declared valid after item fit and demographic bias analysis. The reliability value is high, with a personal reliability coefficient of 0.87 and an item reliability coefficient of 0.99. Internal consistency is also strong, with a Cronbach's Alpha of 0.90. Wright Map analysis shows that the level of item difficulty is below the student's ability, so the scale is easy to apply. This study confirms that the growth scale is considered relevant to measure the growth of prospective educator students. Further development is recommended to respond to cross-cultural issues so that the scale makes more sense in the context of higher education.